VD_FINDINFO Arrêt / 2014 / 516 vom 24. Juli 2014 - VD Tribunal cantonal (2014)
PLACEMENT À DES FINS D'ASSISTANCE, SUPPRESSIONEN GÉNÉRAL, ADMISSION DE LA DEMANDE | 426 al. 3 CC, 426 CC, 450 CC, 450e CC